Web Client and Web Server approaches to Prevent XSS Attacks (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Websites rely completely on complex web applications to deliver content to all users according to set preferences and specific needs. In this manner organizations provide better value to their customers and prospects. Dynamic websites suffer from various vulnerabilities rendering organizations helpless and prone to cross site scripting attacks. Cross Site Scripting attacks are difficult to detect because they are executed as a background process. Cross Site Scripting is the most common web vulnerabilities in existence today which is most exploited issue .In this paper we have presented various approaches used by clients and Server to prevent XSS attacks